Childhood disadvantage and emergency admission rates for common presentations in London: an exploratory analysis. Issue 3 (29th September 2010) - Kyle, Richard G; Kukanova, Marina; Campbell, Malcolm; Wolfe, Ingrid; Powell, Peter; Callery, Peter
Abstract : Aim: To determine whether emergency hospital admission rates (EAR) for common paediatric conditions in Greater London are associated with measures of child well-being and deprivation. Design: Retrospective analysis of hospital episode statistics and secondary analysis of the Index of Multiple Deprivation (IMD) 2007 and Local Index of Child Well-Being (CWI) 2009. Setting: 31 Greater London primary care trusts (PCTs). Outcome measures: EAR in PCTs for breathing difficulty, feverish illness and/or diarrhoea. Results: 24 481 children under 15 years of age were discharged following emergency admission for breathing difficulty, feverish illness and/or diarrhoea during 2007/2008. The EAR for breathing difficulty was associated with the IMD (Spearman's rho 0.59, p<0.001) and IMD indicators of: overcrowding (Spearman's rho 0.62, p<0.001), houses in poor condition (Spearman's rho 0.55, p=0.001), air quality (Spearman's rho 0.53, p=0.002), homelessness (Spearman's rho 0.44, p=0.013), and domains of the CWI: housing (Spearman's rho 0.64, p<0.001), children in need (Spearman's rho 0.62, p<0.001), material (Spearman's rho 0.58, p=0.001) and environment (Spearman's rho 0.53, p=0.002). There were no statistically significant relationships between the EAR of children admitted for feverish illness and diarrhoea or aged under 1 year for any condition, and the IMD, either IMD indicators or CWI domains. Conclusions: Housing and environmental factors are associated with children's demand for hospital admission for breathing difficulty. Some associations are stronger with the CWI than the IMD. The CWI has potential to identify priority PCTs for housing and environment interventions that could have specific public health benefits for respiratory conditions.